Association of four antigens of the tetraspans family (CD37, CD53, TAPA-1, and R2/C33) with MHC class II glycoproteins - Angelisová, P; Hilgert, I; Horejsí, V (Immunogenetics, 1994)
Four of the tetraspans family antigens expressed in B cells, CD37, CD53, TAPA-1, and R2/C33, as well as at least two other molecules, CD19 and CD21, coprecipitate with DR antigens from mild detergent lysates of human B-cell lines and tonsillar B cells. Coprecipitation and preclearing experiments indicate the existence of large multicomponent complexes containing jointly the seven components, although some "incomplete" complexes lacking some of the components may also exist. The complexes contain only a relatively small fraction of the total cellular pool of relevant molecules. The existence of these "tetraspans-DR complexes" may be related to the previously reported antiproliferative and signaling effects of antibodies against most of their components.
Keywords: glykoproteiny; HLA-DR antigeny; Cell Line; monoklonální protilátky; antigeny povrchové; western blotting; Antigens, CD; membránové proteiny; CD antigeny; HLA-DR Antigens; membránové glykoproteiny; antigeny nádorové; protein Kangai-1; Membrane Proteins; B-lymfocyty; Proto-Oncogene Proteins; diferenciační antigeny T-lymfocytů; Tetraspanin 28; Glycoproteins; Precipitin Tests; tetraspaniny; Tetraspanin 25; Blotting, Western; antigeny CD53; lidé; antigeny CD81; Humans; diferenciační antigeny; precipitinové testy; Membrane Glycoproteins; Antigens, Surface; Antigens, Neoplasm; buněčné linie; Antigens, Differentiation; B-Lymphocytes; Tetraspanins; Antibodies, Monoclonal; Antigens, Differentiation, T-Lymphocyte; Kangai-1 Protein; protoonkogenní proteiny